The biological function of Urtica spp. and its application in poultry, fish and livestock - Gao, Yang; Yang, Xuexi; Chen, Bo; Leng, Huan; Zhang, Jize (Frontiers in Veterinary Science, 2024)
Urtica species is an angiosperm plant in the Urticaceae family. It serves as a traditional food and medicinal herb, possessing high nutritional value and various bioactive compounds, including polysaccharides, flavonoids, and polyphenolic compounds. In the realm of animal feeds, Urtica spp. can replace traditional protein feed sources and high-quality forage, thereby reducing feed costs. Moreover, Urtica spp. extract exhibits antioxidant and anti-inflammatory properties and boosts immune regulation. Hence, Urtica spp. plays a beneficial role in enhancing animal performance and improving their immune function. Recently, with the development of sustainable farming techniques, the demand for feed additives that prioritize safety, the absence of drug residues, and environmental friendliness have grown. Consequently, Urtica spp. and its extracts have received widespread attention in animal production. This article summarizes the biological functions of Urtica spp. and its application in animal husbandry while also outlining future prospects for its application. It will provide a scientific basis and reference point for the application of Urtica spp. in animal health and breeding.